1998
DOI: 10.1121/1.421302
|View full text |Cite
|
Sign up to set email alerts
|

Signal processing of the echo signatures returned by submerged shells insonified by dolphin “clicks:” Active classification

Abstract: A large set of dolphin-emitted acoustic pulses ("echolocation clicks") have been examined, which were reflected from various elastic shells that were suspended, underwater, 4.5 m in front of the animal in a large test site in Kaneohe Bay, Hawaii. A carefully instrumented analog-to-digital system continuously captured the emitted clicks and also the returned, backscattered echoes (A/D conversion at 500 kHz). Using standard conditioning techniques and food reinforces, the dolphin is taught to push an underwater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…The subject probably relies on multiple cues at many frequencies from the target echo to conduct discrimination. Although there may be many cues that odontocetes use for target discrimination (Branstetter et al, 2007;Gaunaurd et al, 1998;Muller et al, 2008), the use of high frequencies is very likely to be the most important, and the link between high-frequency hearing loss and a reduction in discrimination performance cannot be ignored. These data strongly suggest that the high-frequency component of echoes provides a great deal of information for fine-scale discrimination Part of the explanation for a reduction in discrimination abilities may also be attributable to the second part of the odontocete sonar system: the click production mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subject probably relies on multiple cues at many frequencies from the target echo to conduct discrimination. Although there may be many cues that odontocetes use for target discrimination (Branstetter et al, 2007;Gaunaurd et al, 1998;Muller et al, 2008), the use of high frequencies is very likely to be the most important, and the link between high-frequency hearing loss and a reduction in discrimination performance cannot be ignored. These data strongly suggest that the high-frequency component of echoes provides a great deal of information for fine-scale discrimination Part of the explanation for a reduction in discrimination abilities may also be attributable to the second part of the odontocete sonar system: the click production mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Much of this effort has been based on the demonstrated ability of odontocetes to differentiate small differences between arbitrarily constructed echolocation targets, including differences in target size, shape and materials from which they are constructed (Nachtigall, 1980). The full suite of cues that odontocetes use to discriminate targets is unknown, but it is thought that they may use small differences in the complex structure of target echoes to differentiate targets (Branstetter et al, 2007;Gaunaurd et al, 1998;Muller et al, 2008). The ability of cetaceans to differentiate and recognize the acoustic characteristics of objects using echolocation has an obvious biological benefit.…”
Section: Introductionmentioning
confidence: 99%
“…Under substantial constraints, some models have been successful at producing information from echoes that could be interpreted in terms of object features (Gaunaurd, Brill, Huang, Moore, & Strifors, 1998). Therefore, dolphins may be able to represent echoically perceived objects in an image-like way.…”
Section: Extracting Object Features From Echo Featuresmentioning
confidence: 99%
“…Indeed the functional bandwidth of other dolphins could be different depending on the animal's hearing abilities, echolocation strategies, and habitat. However, previous studies on the time frequency content of scattered dolphin waveforms did not examine this restriction [1] [8]. Each of the time-frequency tile plots of the atoms is truncated to indicate the relevant frequencies within animal's functional bandwidth.…”
Section: Functional Bandwidthmentioning
confidence: 99%
“…Au [3] hypothesized that the use of short-time frequency analysis may be a plausible method for target discrimination. Time-frequency analysis of dolphin echolocation signals provides a time-evolving representation of the signal frequency content as reported by Gaunaurd et al [8] who used a Wigner-Ville representation. Muller et al [1] reported that four classes of echolocation clicks are involved in the echolocation process of the Tursiops truncatus; moreover, the specific role of the different classes is not well understood.…”
Section: Introductionmentioning
confidence: 99%